Proceedings Ninth International Symposium on Software Reliability Engineering (Cat. No.98TB100257)
DOI: 10.1109/issre.1998.730892
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for detection and estimation of software aging

Abstract: The phenomenon of software aging refers to the accumulation of errors during the execution of the software which eventually results in it's crash/hang failure. A gradual performance degradation may also accompany software aging. Pro-active fault management techniques such as "Software rejuvenation" [9] may be used to counteract aging if it exists. In this paper, we propose a methodology for detection and estimation of aging in the UNIX operating system. First, we present the design and implementation of an SNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
0
1

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(175 citation statements)
references
References 19 publications
2
172
0
1
Order By: Relevance
“…For structural engineering, geometry is important (Kent and Noss 2002). In pure mathematics, basic topics such as numbers, formulae, algebraic and differential equations, vectors, and tensors are vital to engineering (Garg et al 1998). …”
Section: Aspects Of Science Technology Engineering and Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For structural engineering, geometry is important (Kent and Noss 2002). In pure mathematics, basic topics such as numbers, formulae, algebraic and differential equations, vectors, and tensors are vital to engineering (Garg et al 1998). …”
Section: Aspects Of Science Technology Engineering and Mathematicsmentioning
confidence: 99%
“…Numerous studies demonstrate that engineering students struggle with a wide range of areas of mathematics, including algebra, matrices, logarithms, analytic skills, trigonometry, calculus, proof, logic, modeling, and problem-solving (Bernstein 2005;Garg et al 1998;Shatz 2016). A study by Faulkner et al (2016) found out that students' mathematical competencies had decreased.…”
Section: Aspects Of Science Technology Engineering and Mathematicsmentioning
confidence: 99%
“…Empirical confirmation demonstrated free space shows most brief Time to Exhaustion (TTE) among computers resources [31], and space administration faults are a noteworthy reason for crashes [32]. Therefore, numerous studies on aging and renewal analyses program aging phenomena influencing free space, by measuring quantity of free physical space and swap space [33], and a few estimation based methodologies apply time arrangement and measurable models to these variables.…”
Section: Space Utilizationmentioning
confidence: 99%
“…In [31], a system of UNIX workstations was checked to distinguish aging patterns in utilization of a few resources (identified with simulated space, OS portion, file computers, disk, and organize), and critical aging pattern was seen in procedure [52]. These two perspectives are most regular issues happening in non-safety-critical computers and they are considered by an expanding number of SAR studies.…”
Section: Space Utilizationmentioning
confidence: 99%
See 1 more Smart Citation